Android Platform using e-Voting System - Tote, Abhijeet M (Journal of Advanced Research in Signal Processing and Applications, 2021)
The foremost motive of e-voting is to choose the leader or candidate of people’s choice. Many countries face the difficulties in the procedure of voting such as ridging votes during election, insecure or inaccessible polling stations, insufficient polling materials and also not experience personally. To overcome the above drawbacks online voting or polling system is proposed. To get acquainted with the system, the users, citizens shall be trained on how to vote online prior to the election. The e-Voting system will permit the casting of electronic ballots from almost any location about the world. The first phase called ID2E is made for testing the viability for international voting by means of SMS protocol along with the tools such as web 2.0 to create a platform for discussion about election main theme. The second phase is construction of voting prototype using android Smartphone, submissions and databases to collect the vote that are obtainable on dynamic web page. Online voting system can be used to give the precise consequences of votes to reveal precise voter penchants. How to cite this article: Tote AM, Gaawande RM. Android Platform using e-Voting System. J Adv Res Sig Proc Appl 2019; 1(2): 5-8